Repoliticizing the Religious: The Catholic-Inspired Neoconservative Mobilization against Moral Politics From The Post-secularity Framework - García Martín, Joseba; Perugorría, Ignacia ('Ilu. Revista de Ciencias de las Religiones, 2025)
Controversies over so-called 'moral policies' have gained increasing visibility in Spain over the last decades. In the face of these policies, enacted amidst a steep process of secularization, a field of Catholic-inspired laity organizations with a neo-conservative ideology (CISO-N) has emerged to defend the Catholic normative framework. Waging a double battle, cultural and political, these organizations provide new angles to analyze the relationship between religion and politics from the theoretical perspective of post-secularity. CISO-Ns deprivatize Catholicism in the public sphere through strategically secularized protest repertoires and discursive frames. They thus align with the Vatican strategy of ‘new evangelisation’, which promotes a «veiled re-Christianization» of institutions and society protagonized by the laity. CISO-N members can thus be characterized as ‘citizen-believers’ and activists. Drawing on the literature on post-secularization and social movements, and on a 7-year qualitative study, we trace the protest cycle and evolving organizational structure of the OLIC-N field over a 40-year period. Next, we compare two protest events organized by the OLIC-N «moderate» and «radicalized» blocs during the last phase of the cycle, characterized by increasing levels of 'affective polarization' caused by the «mainstreaming» of feminist postulates, and the institutionalization of 'cultural backlash' dynamics since the arrival of VOX to political institutions. Our data show that the mobilization of the 'organized laity' is not always, or not necessarily, an «ally» of the pluralization of democratic systems, indicating the need to rethink some of the postulates of postsecularization.
Keywords: catholicism; mobilization; moral policies; strategic secularism; postsecularism; public sphere